Consumers' Complaints, the Nature of Corruption, and Social Welfare - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2013)
A primary means of bureaucratic oversight is consumer complaints. Yet, this important control mechanism has received very little attention in the literature on corruption. I study a model of corruption with incomplete information in which consumers require a government service from officials who may be corrupt. A victim of corruption can report corrupt officials to higher-ranking officials (supervisors) who may be corrupt or honest. I find that social welfare may be non-monotonic in the proportion of honest supervisors. In some cases, an increase in the proportion of honest supervisors increases social welfare only if there is a critical mass of honest supervisors. Under certain conditions, there is, surprisingly, an equilibrium in which no one reports corruption regardless of the proportion of honest supervisors although all lower-ranking officials are corrupt. The analysis shows that using an increase in consumer complaints as a measure of the success of an anti-corruption campaign may be wrong because the consumers may benefit in other ways (e.g., a fall in the equilibrium bribe). I also fill a gap in the literature by endogenizing an official's decision to engage in corruption with theft or corruption without theft as defined by Shleifer and Vishny (1993) and use the model to shed light on recent anticorruption initiatives such as the Punjab Citizen Feedback Model in Pakistan and a recent proposal by Kaushik Basu (2012).
Keywords: H80; K42; 330; bribes; consumer complaints; corruption with theft; corruption without theft; Bayesian equilibrium